Alkyne-Based Cascade Strategies for the Construction of Diverse Carbo/Heterocycles - Srinivas, Dasari; Dakoju, Ravi Kishore; Chinnabattigalla, Sreenivasulu; Satyanarayana, Gedu (Synlett, 2025)
Carbocycles/heterocycles are fundamental structural motifs in natural products, pharmaceuticals, and functional materials. Alkyne-based cascade strategies have emerged as powerful tools for the efficient construction of these frameworks, enabling rapid access to diverse ring systems through domino cyclization pathways. This account highlights the representative recent advances of alkyne-mediated cascade reactions, covering transition-metal catalysis and acid-mediated reactions. These methods facilitate multiple bond-forming events in a single operation, offering high atom and step economy. Special focus is given to illustrative transformations, mechanistic insights, and the broad utility of alkynes as precursors for the concise synthesis of diverse carbocyclic and heterocyclic molecular frameworks.
Keywords: Carbocyclic; Heterocyclic; Domino; Cascade; Cyclization; Alkyne